Simulation of the effectiveness evaluation process of security systems; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Godovykh A. V. Aleksey Valeryevich; Stepanov B. P. Boris Pavlovich; Sheveleva A. A.; Sharafieva K. R. (2016, 2016)
Title screen